Antimicrobial properties of different fractions of Swertia Chirata / Nik Aiman Afiq Nik Ab Rahman, Isma Syahril Ismail and Lwin Lwin Nyein - Ismail, Isma Syahril; Lwin, Lwin Nyein (Faculty of Business Management, 2013)
Complementary and alternative medicine (CAM) is becoming increasingly popular and experienced a high growth all over the world. A medicinal plant, Swertia chirata, has been widely use as herbal medicine in Asian countries and some parts of the world. The aim of this study was to evaluate the antibacterial properties of Swertia chirata and to assess the cytotoxicity using brine shrimp lethality test. Plants were extracted using ethanol. Disc diffusion technique was used to determine antimicrobial activity. Crude extraction of the whole plant showed significant antimicrobial activities against some clinical bacterial isolates. Plant extracts at a concentration of 100 μg disc-1 were used to evaluate the antimicrobial activity and 30 μg disc-1 concentration of Chloramphenicol was used as a positive control. Zone of inhibition against Staphylococcus aureus, Bacillus cereus, Escherichia coli and Salmonella arizonae were 10 mm, 6 mm, 9 mm and 7 mm respectively. Minimum Inhibitory Concentration (MIC) of the crude extract was determined by serial dilution technique which showed 128 μg/ml, 64 μg/ml, 128 μg/ml and 128 μg/ml respectively. Plant showed no significant cytotoxitcity with LC50 >5000 μg.The results obtained revealed inhibition against some gram positive and gram negative bacteria and low cytotoxicity value indicates its effective use as traditional medicine plant. Thus, Swertia chirata which possesses antimicrobial activity, with low cytotoxicity, will be of use in complementing a standard antimicrobial drug and will contribute to the current status of the public health where emergence of drug resistance is a major problem.